2010
DOI: 10.1088/2041-8205/716/1/l31
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the Optical/Ultraviolet Variability on the Emission-Line Properties and Eddington Ratio in Active Galactic Nuclei

Abstract: The dependence of the long-term optical/UV variability on the spectral and the fundamental physical parameters for radio-quiet active galactic nuclei (AGNs) is investigated. The multi-epoch repeated photometric scanning data in the Stripe-82 region of the Sloan Digital Sky Survey (SDSS) are exploited for two comparative AGN samples (mostly quasars) selected therein, a broad-line Seyfert 1 (BLS1) type sample and a narrow-line Seyfert 1 (NLS1) type AGN sample within redshifts 0.3-0.8. Their spectral parameters a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
85
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(107 citation statements)
references
References 31 publications
22
85
0
Order By: Relevance
“…If L bol /L Edd is an (at least crude) estimate of the accretion rate, both weak emission lines (but strong Fe ii pseudo-continuum) and small variability amplitudes are the consequence of strong accretion. An anticorrelation with variability is plausible because, if the accretion rate is high, the region emitting the continuum observed in a given passband is larger and the variability amplitudes are consequently smaller than in the case of a low accretion rate (Ai et al 2010). Wilhite et al (2008) proposed that the accretion rate is high and the variability is small for optically young quasars, i.e., when they become visible in the optical.…”
Section: Special Quasar Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…If L bol /L Edd is an (at least crude) estimate of the accretion rate, both weak emission lines (but strong Fe ii pseudo-continuum) and small variability amplitudes are the consequence of strong accretion. An anticorrelation with variability is plausible because, if the accretion rate is high, the region emitting the continuum observed in a given passband is larger and the variability amplitudes are consequently smaller than in the case of a low accretion rate (Ai et al 2010). Wilhite et al (2008) proposed that the accretion rate is high and the variability is small for optically young quasars, i.e., when they become visible in the optical.…”
Section: Special Quasar Typesmentioning
confidence: 99%
“…Numerous studies have shown that the optical/UV continuum variability of quasars correlates with various physical parameters such as time-lag, rest-frame wavelength, luminosity, radio properties, emission line properties, and the Eddington ratio (e.g., Ulrich et al 1997;Giveon 1999;Helfand 2001;Gaskell & Klimek 2003;Vanden Berk et al 2004;Rengstorf et al 2006;Wold et al 2007;Wilhite et al 2008;Bauer et al 2009;Ai et al 2010;MacLeod et al 2010;Schmidt et al 2010). Despite considerable progress in the description of quasar variability, there are still conflicting claims about these correlations and their physical interpretation is fraught with problems.…”
Section: Introductionmentioning
confidence: 99%
“…The BWB trend has also been found in radio-quiet AGNs, for which the variability was found to be anti-correlated with the Eddington ratio (Pu et al 2006;Ai et al 2010). In radioquiet AGNs, the optical variability could be due to the variation in the accretion process, for example, the variation in the accretion rate (e.g., Li & Cao 2008), since the jet is either weak or absent.…”
Section: Ssrqs and Fsrqsmentioning
confidence: 67%
“…Both the long-term or short-term variabilities of radio-quiet AGNs have also been explored (e.g., Stalin et al 2004Stalin et al , 2005Gupta & Joshi 2005;Ai et al 2010). The accretion disk instabilities might explain the optical microvariability of radio quiet AGNs (e.g., Gopal-Krishna et al 1995; see also Gopal-Krishna et al 2003, for alternative scenario).…”
Section: Introductionmentioning
confidence: 99%
“…To measure the variability amplitude in each filter band for each quasar, we adopt the formalism similar to that used in Ai et al (2010) and Sesar et al (2007):…”
Section: Variability Estimationmentioning
confidence: 99%